The Development of a Prison Mental Health Unit in England: Understanding Realist Context(s) - Biddle, Paul (2020)
A pragmatic solution for the provision of care for prisoners with serious mental illness, who are often subject to delays in hospital transfer, is the creation of specialist prison units. This paper analyses the development of a prison unit in England for prisoners with ‘serious mental illness’. The unit was developed within over-lapping health and justice contexts, including expectations, pressures and priorities, which impacted on the outcomes expected and achieved. The methodology included attendance at Steering group meetings, analysis of a minimum dataset, and interviews with key stakeholders. A number of key sites of contestation are analyzed including: admission criteria; aims; activities; staffing; the physical environment; and discharge